COMPLETE AUDIT CYCLE: PULMONARY EMBOLISM AMBULATORY CARE PROTOCOL - AHMED, M; SADIQ, HZ; NAYYAR, MA; QURBAN, A; MALIK, M; RIZVI, AZ; MUNAWAR, MU; RABBANI, M; SUFYAN, M (Biological and Clinical Sciences Research Journal, 2024)
A significant number of patients present to acute medical services with chest pain. Pulmonary Embolism (PE) is a crucial differential diagnosis in such cases. Recent research has enabled the ambulatory management of low-risk patients, a strategy increasingly adopted by hospitals globally. Hospitals like Bahria Town International Hospital in Pakistan have implemented ambulatory pathways to manage these cases efficiently. This article reports a comprehensive audit of our PE ambulatory care protocol (PE Pathway). Methodology: The audit was conducted in the Department of Critical Care at Bahria Town International Hospital, Pakistan. We prospectively analyzed manual and electronic records of all patients presenting with chest pain and managed in this department. The initial audit cycle reviewed patients from 1st January to 31st March 2023, while a second audit was conducted from 1st April 2023 to 9th June 2023. Results: 31 adult patients were reviewed in the first cycle, and 46 patients were assessed in the second. Both manual and electronic records were analyzed. The initial audit revealed that the completion rate of the Pulmonary Embolism Severity Index (PESI) score was low. However, all patients received initial anticoagulation doses. Necessary investigations, including blood tests, chest X-rays, and electrocardiograms (ECG), were completed promptly at the time of referral from the Emergency Department (ED) to the Department of Critical Care. Computed Tomography Pulmonary Angiograms (CTPA) or Ventilation Perfusion (V/Q) scans were also requested and discussed with radiologists on the same day or the following day. A key issue identified was a lack of clear follow-up instructions for Out of Hours (OOH) referrals from the ED to the Department of Critical Care, which led to patient anxiety and confusion regarding their care. To address this, we implemented improvements in the PE Pathway documentation, ensuring that the PESI score was consistently completed and providing clear follow-up instructions for OOH referrals. The re-audit demonstrated significant improvements in compliance with documentation and the appropriateness of referrals. All OOH referrals were promptly picked up the next day, and no patients were lost to follow-up during the study period. Moreover, the number of patients managed through the PE Pathway increased by 50%, leading to the avoidance of unnecessary admissions. Conclusion: The data from this audit demonstrate that ambulatory care pathways for low-risk PE patients can be successfully applied in Pakistan. The protocol effectively allocates resources, reduces unnecessary hospital admissions, and enhances patient satisfaction by providing timely and appropriate care. The findings support the continued use and refinement of such pathways to improve patient outcomes and resource utilization.